KEPEMIMPINAN DIGITAL: MENGELOLA INSTITUSI PENDIDIKAN DI ERA POSTDIGITAL - Donny Charles Chandra; Gidion Hary Susanto; Theresia Pangalinan; Oen Yehuda Petrus Ariel (Bethel Press, 2021)
This study aims to explore the role of digital leadership in managing educational institutions in the postdigital era through a library research approach. The postdigital era is characterized by the intricate interconnection between technology, humans, and social contexts, which transforms the ways of learning, teaching, and managing educational institutions. Data were collected through an extensive review of scholarly books, peer-reviewed journal articles, international policy reports, and previous research published up to 2021. The analysis was conducted using content analysis to identify key themes related to leadership transformation, strategic roles in educational governance, as well as ethical challenges and capacity building. The findings reveal that digital leadership plays a pivotal role as a driver of change, shifting the focus from mere technology adoption toward the development of an adaptive, data-informed, and inclusive learning culture. The main challenges lie in ethical issues such as data privacy, algorithmic bias, and digital inequality, which demand responsive and integrity-driven leadership. In conclusion, the success of educational transformation in the postdigital era largely depends on leaders who can integrate technology with human values, foster innovative cultures, and strengthen the capacities of all stakeholders. This study provides a conceptual framework relevant for guiding educational leadership policies and practices in navigating ongoing technological and social dynamics.